UPM - ExxonMobil bid to conserve forest reserves - New Sunday Times, (2011)
KUALA LUMPUR : ExxonMobil subdiaries in Malaysia will plant 5,000 seedlings at the Ayer Hitam Forest Reserves in Puchong by next year under the company's community project.